Marx's Hypotheses on the Length of the Working Day - West, Edwin G. (Journal of Political Economy, 1983)
In order to argue that value depends exclusively on labor, Marx had to assume a uniform rate of surplus value (exploitation) across all industries. But if this rate of exploitation is the same everywhere, hours of work have also to be uniform. Marx accordingly insisted that this was so and quoted contemporary evidence in support. A close examination of his sources (nineteenth-century factory inspectors' reports) fails, however, to confirm his prediction. Instead the data are more consistent with the competing neoclassical hypothesis, originating with Jevons, that work hours will vary because workers' labor and leisure preferences vary.